2004
DOI: 10.1161/01.res.0000117070.86556.9f
|View full text |Cite
|
Sign up to set email alerts
|

B-Type Natriuretic Peptide Exerts Broad Functional Opposition to Transforming Growth Factor-β in Primary Human Cardiac Fibroblasts

Abstract: Abstract-The natriuretic peptides, including human B-type natriuretic peptide (BNP), have been implicated in the regulation of cardiac remodeling. Because transforming growth factor-␤ (TGF-␤) is associated with profibrotic processes in heart failure, we tested whether BNP could inhibit TGF-␤-induced effects on primary human cardiac fibroblasts. BNP inhibited TGF-␤-induced cell proliferation as well as the production of collagen 1 and fibronectin proteins as measured by Western blot analysis. cDNA microarray an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
169
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(182 citation statements)
references
References 49 publications
(35 reference statements)
7
169
0
5
Order By: Relevance
“…TGF-␤ treatment is known to enhance the profibrotic state by altering expression of proteins such as plasminogen activator inhibitor (PAI-1) and IL-6 (28,29). Consistent with the ability of increased AC expression to blunt collagen synthesis, overexpression of AC6 decreased basal and TGF-␤-regulated expression of PAI-1 by 89 Ϯ 3% and 59 Ϯ 8%, respectively, and IL-6 by 81 Ϯ 2% and 92 Ϯ 3%, respectively.…”
Section: Ac6 Overexpression Enhances Forskolin-and Adrenomedullin-stimentioning
confidence: 78%
“…TGF-␤ treatment is known to enhance the profibrotic state by altering expression of proteins such as plasminogen activator inhibitor (PAI-1) and IL-6 (28,29). Consistent with the ability of increased AC expression to blunt collagen synthesis, overexpression of AC6 decreased basal and TGF-␤-regulated expression of PAI-1 by 89 Ϯ 3% and 59 Ϯ 8%, respectively, and IL-6 by 81 Ϯ 2% and 92 Ϯ 3%, respectively.…”
Section: Ac6 Overexpression Enhances Forskolin-and Adrenomedullin-stimentioning
confidence: 78%
“…Furthermore, lysyl oxidase (LOX) is also instrumental during collagen biogenesis that catalyzes lysine-derived cross-bridges between two or more lysine residues of nascent procollagen peptides during their maturation into collagen molecules (5, 7). Altered and deregulated expression of these factors has been demonstrated in failing myocardium (5).Involvement of various neurohumoral and growth factors has also been illustrated in the development of cardiac fibrosis both in vitro and in vivo (3,8). Cellular cross-talk between AngII-treated cardiomyocytes and fibroblasts has been shown to play an important role during collagen up-regulation with involvement of IL-6 during fibrosis (8 -10).…”
mentioning
confidence: 99%
“…Involvement of various neurohumoral and growth factors has also been illustrated in the development of cardiac fibrosis both in vitro and in vivo (3,8). Cellular cross-talk between AngII-treated cardiomyocytes and fibroblasts has been shown to play an important role during collagen up-regulation with involvement of IL-6 during fibrosis (8 -10).…”
mentioning
confidence: 99%
“…It was of interest that transforming growth factor-β (TGF-β) was under-expressed in young HHR. A recent study has shown that human B-type natriuretic peptide (BNP) inhibits TGF-β-induced effects on primary human cardiac fibroblasts, including down-regulating TGF-β-regulated genes related to fibrosis, myofibroblast conversion, proliferation, and inflammation (33). The mouse homologue to the polypeptide hormone BNP, natriuretic peptide precursor type B (Nppb), was over-expressed in both young and old HHR, and several matrix/structural protein-related genes (β-actin, Actb; procollagen-5, Col5a1; cartilage associated protein, Crtap) were under-expressed in young HHR.…”
Section: Discussionmentioning
confidence: 99%